Nursing care regarding the psycho-emotional aspects of women submitted to mastectomy - Bernardino, Amanda de Oliveira; Silva, Matheus Vinicius Barbosa da; Ferreira Filho, Edite Barbosa; Silva, Francisco de Assis da; Silva, Polyana Maccoy e; dos Santos Lima, Rosana (ABCS Health Sciences, 2024)
Breast cancer, or breast neoplasm, is one of the most frequent types of cancer, and one of the most prevalent among women. The diagnosis and specific treatments, such as mastectomy surgery, lead women to experience different feelings, with the most predominant negative thoughts. In this way, the objective of this study is to describe the importance of nursing care in the face of the psycho-emotional aspects of women after mastectomy. This is an integrative literature review study, developed in electronic Medline and Lilacs databases. The following terms were used: Breast neoplasm; Nursing; Emotions; Mastectomy. A total of 2,314 articles were found, of which eight were selected. The results and discussions were divided into two thematic axes: The first deals with the emotions of women after mastectomy, whose feelings arising from the diagnosis of the disease start to affect different areas, such as personality, sexuality, family, and social relationships. Furthermore, the second deals with nursing care after mastectomy, which must be conducted integrally, aiming at restoring physical and emotional health. Nursing is the vehicle capable of planning and collaborating with these women, promoting humanized treatment and assistance, oriented and aimed at a better quality of life, and stimulating self-help, self-esteem, and acceptance of their body.